ANALISIS FAKTOR PENGHAMBAT TERPENUHINYA KUOTA REPRESENTASI PEREMPUAN DI DEWAN PERWAKILAN RAKYAT DAERAH PROVINSI SUMATERA SELATAN - DAULAT NATHANAEL BANJARNAHOR (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2020)
One of the basic principles affirmed in the 1945 Constitution is the principle of equality in law and government. But in reality it can be seen that the representation of women in the legislative body in Indonesia in general and the legislative body in the province of South Sumatra in particular has not reached 30 (thirty) percent.The purpose of this study was to analyze the factors causing the non-fulfillment of women's representation quota along with the inhibiting factors to realize the women's representation quota in the legislative body, DPRD of South Sumatra Province. The conclusion of this research, which causes the non-fulfillment of quota of representation of women in legislative bodies is the problem in the regeneration of political parties, the problem of political stigma that is not good in the community, and there is no clear legal substance, strict sanctions related to legal rules related to representation quota women. The obstacles that arise in realizing the 30 percent quota for women's representation in legislative bodies come from patriarchal culture that is still thick in social life, political parties that do not consider women's representation as important, and have minimal socialization from the government and political parties regarding women's representation. Therefore, the authors suggest that political parties take a more active role in the process of political cadre formation towards women, improving the cadre guidance program, in order to attract women to enter and become political party cadres. Legislation related to legislative elections should be reviewed to clarify the quota for women's representation, and women must be more sensitive to their own people, so that it is hoped that women will be willing to enter politics to fight for the fate of women. the fulfillment of the expected representation of women can be realized.